Pengaruh Suhu dan Lama Pengeringan terhadap Karakteristik Kimia dan Sensoris Permen Jelly Pepaya (Carica Papaya L.) - Novita Pandesolang; Lana E. Lalujan; Yoakhim Oessoe (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
The purpose of this study was to analyze the effect of temperature and drying time on the characteristics of the chemical componens of papaya jelly candy and evaluate the level of preference for papaya jelly candy that is dried at different temperatures and drying times. This study used a completely randomized design (CRD) method which consisted of four treatments and three repetitions with different temperatures and drying times, namely : treatment drying using room temperature for 48 hours; drying at 40°C for 36 hour; drying at 50°C for 24 hours; and drying at 60°C for 8 hours o’clock. The resut of this study indicate that differences in temperature and drying time produce papaya jelly candy with chemical characteristics, namely water content (10.49% - 23.73%), sucrose (13.78% - 16.25), and pH (6.17% – 5,35%). The papaya jelly candy with the most preffered color, aroma, taste, and texture by the panelists was dried at room temperature for 48 hours. Keywords: jelly candy; papaya; drying; sucrose.